Characteristics and survival in bone metastatic breast cancer patients with different hormone receptor status: A population-based cohort study - Jiang, Xiaofan; Chen, Guanglei; Sun, Lisha; Liu, Chao; Zhang, Yu; Liu, Mingxin; Liu, Caigang (Frontiers in Oncology, 2022)
Background Accumulating preclinical evidence has uncovered the indispensable role of steroid hormone and their receptors, namely estrogen receptor (ER) and progesterone receptor (PR), in the development of bone metastases in breast cancer. Limited data are available regarding the survival difference between different hormone receptor (HR) subgroups, and its prognostic significance is uncertain now. Such data is important for risk stratification and needed to formulate specialized regimen for bone metastatic breast cancer. Methods From the year of diagnosis 2010 to 2018, 554,585 breast cancer patients, among which 19,439 with bone metastasis and 10,447 with bone-only metastasis, were extracted from the Surveillance, Epidemiology, and End Results (SEER) database. Kaplan-Meier survival analysis was performed to compare the survival difference between the different HR status subgroups. Univariate and multivariate Cox proportional hazard regression was used to validate the prognostic role of HR status, and identify other prognostic factors in bone metastatic breast cancer. Results ER-positive/PR-positive breast cancer patients with bone metastasis showed the best breast cancer-specific survival (BCSS) and overall survival (OS) than those with other HR statuses, while single PR-positive bone metastatic breast cancers manifest similar survival with ER-negative/PR-negative ones. Adjusted Cox regression analysis demonstrated that patients with older age, male, black race, ILC, higher tumor grade, T3-T4, HER2 negative status, absence of surgery or adjuvant treatment, and HR status other than ER-positive/PR-positive tended to have worse outcomes. Further subgroup analysis based on HER2 status showed that within HER2-positive breast cancers, ER-positive/PR-positive ones still manifest better survival than the other three HR status subgroups, which are similar in survival outcomes. Conclusion Though collectively viewed as HR-positive breast cancers, certain distinctions exist between bone metastatic breast cancers with different HR statuses in survival outcome. Our findings indicate that despite metastasizing to the same location, the different survival rate is determined by the HR status of breast cancer. Selection and intensity of the regimen should consider HR status, and HER2 status occasionally, when treating bone metastatic breast cancer.